Participatory Culture and the Death of Cyberflânerie in Tao Lin’s Taipei - Adil Hussain (Asiatic: IIUM Journal of English Language and Literature, 2025)
This paper examines how Tao Lin’s novel Taipei is seen through the lens of the “cyberflânerie,” and how that approach does not critically engage with the text. Cyberflânerie evolved from the twentieth-century concept of flânerie developed by Walter Benjamin and is a modern reinterpretation of the traditional flâneur adapted to the digital age. With social media rendering cyberflânerie impossible, the protagonist in Taipei, Paul, navigates a world in which his identity, consciousness, and interactions are deeply mediated by the Internet and social media. The paper argues that Paul’s experiences reflect a broader cultural shift towards a participatory culture, where individuals simultaneously consume and produce digital content, blurring the lines between producer and consumer (prosumer). The novel is seen as a travelogue of the digital age and how the Internet structures identity, community, and even emotional experiences, often leading to a sense of disconnection and alienation. Engaging with theories from media ecology and participatory culture, the discussion shows how digital technologies shape cognitive and social behaviours, and how the Internet has replaced the passive flâneur with an active participant in a networked society.